CHEMICALAI-INTEGRATED PROBLEM-BASED LEARNING VS GUIDED INQUIRY: ENHANCING STUDENTS’S SCIENTIFIC ARGUMENTATION SKILLS IN REACTION RATES - Putri Riza Abrilia; Munzil; Hadi Nur (Universitas Negeri Surabaya, 2026)
Chemistry education involves complex representations often hindering scientific argumentation. This study compares the effectiveness of Problem-Based Learning (PBL) and Guided Inquiry (GI) integrated with ChemicalAI in enhancing students scientific argumentation skills on reaction rates. The research employed a quasi-experimental method with a pretest-posttest non-equivalent control group design. Data were analyzed using the Rasch Model for instrument validation and Analysis of Covariance (ANCOVA) for hypothesis testing. Rasch analysis confirmed the high reliability of the instrument while identifying reasoning as the most challenging component for the students. Based on the research findings, it was found that students who participated in the PBL method performend significantly better than students who participated in the GI method. This demonstrates superior performance in formulating claim, evidence and reasoning. Furthermore, the integration of Chemical-AI into PBL effectively facilitates the development of complex scientific arguments based on experimental data.